Foundations of global health & human rights - Gostin, Lawrence O. (Lawrence Ogalthorpe) (New York, NY Oxford University Press, 2020)
an rights are essential to global health. Given this interdisciplinary importance, the field of "Health and Human Rights" has proven increasingly consequential in local, national, and global contexts. Academics teach the subject in schools of law, medicine, public health, nursing, social work, international relations, and global studies. Nongovernmental organizations apply human rights in health programming and advocate for human rights in public policy. Policymakers are called upon to find ways to conform health policies, programs, and practices to evolving human rights standards. These human rights norms and principles have become central to health; yet, rising threats in an increasingly divided world have challenged many of these advances. It is necessary to empower a new generation of practitioners to sustain the global commitment to universal rights in public health. Looking to the next generation to face the struggles ahead, this foundational text provides a detailed understanding of the complex relationship between global health and human rights. In preparing the next generation to address future challenges to global health, human rights knowledge will be crucial to influencing health policy, research, and advocacy. Although the rhetoric of "human rights" has long been central to public health engagement, professionals must be able to operationalize the legal obligations of human rights as a basis for public health. It is necessary to accelerate health and human rights education. Academic study of the field can provide a foundation for greater inclusion of human rights in health professional studies and greater inclusion of global health in legal studies- informing a new generation of interdisciplinary professionals in healthrelated human rights, engaging practitioners to revitalize human rights at the center of health practice, and securing a future of global health with justice"--
The birth and development of human rights for health / Benjamin Mason Meier, Thérèse Murphy, and Lawrence O. Gostin -- Global health law : legal foundations for social justice in public health / Lawrence O. Gostin, Matiangai V. S. Sirleaf, and Eric A. Friedman -- The right to health and health-related human rights / John Tobin and Damon Barrett -- The rights-based approach to health / Flavia Bustreo and Curtis F.J. Doebbler -- Translating International Law into Domestic Law, Policy, and Practice / Gillian MacNaughton and Angela Duger -- Human rights advocacy in global health / Joseph J. Amon and Eric Friedman -- Monitoring and review to assess human rights implementation / Benjamin Mason Meier, Hanna Huffstetler, and Judith Bueno de Mesquita -- Justiciability of human rights for health / Colleen M. Flood and Bryan Thomas -- Advancing human rights through global health governance / Benjamin Mason Meier, Margherita Marianna Cinà, and Lawrence O. Gostin -- Communicable diseases, health security, and human rights : from AIDS to Ebola / Sharifah Sekalala and John Harrington -- Human rights and non-communicable diseases : controlling tobacco and promoting healthy diets / Brigit Toebes and David Patterson -- The emergence of "new" health-related human rights : recognizing the human rights to water and sanitation / Benjamin Mason Meier and Inga T. Winkler -- Chronic illness : disability and mental health / Oliver Lewis and Soumitra Pathare -- Equity in health : sexual and reproductive health and rights / Terry McGovern and Aziza Ahmed -- Health and human rights through development : the right to development, rights-based approach to development, and sustainable development goals / Stephen P. Marks and Alice Han -- International trade, public health, and human rights / Chuang-Feng Wu and Chien-Huei Wu -- Health and human rights in conflict and emergencies / Dabney P. Evans, Edward L. Queen, and Lara S. Martin -- Human subjects in globalized health research / Andrés Constantin and Roberto Andorno -- The environment, a changing climate, and planetary health / Alexandra L. Phelan --- Global health and human rights in the age of populism / Lawrence O. Gostin, Andrés Constantin, and Benjamin Mason Meier.
Includes bibliographical references and index.
Keywords: Human rights; Right to health. -- Electronic books